Computer aided silicon padding design for burn injury - Salleh, Mohamed Najib; Acar, Memis; Burns, Neil D. (2013)
This paper reports a computational method to develop silicon padding to be inserted into the low pressure areas of a custom designed pressure garment to obtain a more uniform pressure distribution.The padding was developed by using digital scanned data of patient body. The custom designed paddings and corresponding pressure garments are constructed for a number of subjects, and experimentally tested and verified by comparing the pressure measured using the customized pressure garment with and without padding.The results show that the custom made pressure garment paddings help to increase the pressure close to the specific design pressure in the low pressure regions, leading to a much more uniform pressure application to the whole of the affected body part, which in turn offers an advantage for the healing process and the prevention of the formation of scar tissue due to burn injury.